Why time flies? The role of immersion in short video usage behavior - Yan, Yurong; He, Yingfei; Li, Longfei (Frontiers in Psychology, 2023)
Background: Short videos are becoming increasingly popular globally, and users are devoting more time to viewing them. However, few studies have examined the characteristics of short video content and the technical features that are related to media use. The present study developed a model to explore the influence of technological affordances on short video usage and considered innovation in terms of format, setting, and content. Method: A total of 496 viewers of short videos from China were surveyed. The participants completed 31 Likert-scale items. The study used maximum likelihood estimation modeling. Results: The results revealed that perceived novelty and content value (entertainment and irritation) affected immersion positively, consequently influencing intentions for reuse and recommendation. The ease of navigating an application, narrative structure, and information value had no significant effect on immersion. Conclusion: These findings have confirmed that perceived situation affordance and the affective affordance of short videos in digital environments that are managed by intelligent algorithms. It is necessary to analyze the potential impact of different affordances specifically.